"Dimple"-matically correct - Revisiting the technique for the creation of a chin dimple - N. J. Mokal; M. F. Desai (Indian Journal of Plastic Surgery)
The boom in cosmetic surgery has ushered in the age of the "designer dimple." In the current scenario where an increasing number of Indians are seeking cosmetic surgery, we present our technique for creation of chin dimples. We used this simple and straightforward technique in one patient. The principal steps of the technique include thinning the skin flap, creating a concave indentation in the mandibular symphysis, and obtaining an adhesion between the thinned skin flap and the indented bone. An aesthetically pleasing chin dimple was achieved. We propose that the bony contouring improves the chances of creating a permanent chin cleft or dimple. Our technique for creation of chin dimples aims to give an aesthetic and permanent result by altering the underlying contour of mandibular symphysis and achieving accurate skin coaptation with non-absorbable sutures.